Estrategias de publicidad de la Panadería y Dulcería Flor del Azuay ubicada en la ciudad de Babahoyo, periodo 2022. - Gastesi Rivera, Ney Antonio (2023)
The present case study allowed us to know the need that the Flor del Azuay Bakery and Sweets has by not having an advertising strategy plan, with the need to create strategies to position the company in the market, in addition to loyalty strategies. using the 4p's of marketing such as price, product, place and promotion, which will make it possible to better publicize the products and services offered by the commercial premises. It was also possible to verify the results that were given through the instruments that were used in the present study, the survey being the one that allowed us to know the level of advertising that the commercial premises has maintained up to now and also through the instrument of a comparative matrix where the level of sales of the Flor del Azuay Bakery and Sweets could be known, divided into two semesters that were from January to June and from July to December, taking into account as important data the stationary periods that occurred in each one of the semesters in the 2022 period. In the study carried out, it was possible to conclude, once the marketing strategies were evaluated, that the company will need various means and techniques to strengthen the recognition and loyalty of its clientele to stand out among the competition. Due to the lack of advertising, sales were reduced. which does not allow the growth of the commercial premises. It was recommended to the owner of the establishment to create digital media which will allow the general public to learn about the products and services, which would expand the market and increase sales opportunities.